Simulatian of self diffusion of iron (Fe) and Chromium (Cr) in Liquid lead by Molecular Dynamic - Ernik Dwi S; Artoto Arkundato; Supriyadi Supriyadi; Heru Baskoro; Elva Nurul F (UPT Penerbitan Universitas Jember, 2016)
Number of rectors have become more and more from year to year, and there are currently around 800 reactors operated around the world. Fast breeder reactor then is one of the new types of reactors design, that are still being developed. Then the corrosion resistance of steels used in reactor, is one focus of today researches, due to the corrosive nature of material immersed in high temperature molter liquid metal, as Pb coolant. A strong interaction between the atoms of steels with molten metal at high temperatures causes of occurrence of diffusion processes between the steel and the cooling material. Self diffusion coefficient is a physical parameter that may be used to identify the corrosivity of steel. The choice of using the selected material than is crucial in nuclear reactors design. The corrosion simulations were run using LAMMPS molecular dynamics software. This simulation showed that adding Cr in the FeCr was placed in the center of liquid lead does not have effect for self diffusion of iron.